Renewable adsorbent for removing hydrogen sulfide at low temperature as well as preparation method and application thereof

By using a composite aluminosilicate carrier with a microporous/mesoporous structure and a transition metal oxide active component in the hydrogen sulfide adsorbent, the problems of high temperature, high cost and low accuracy of the hydrogen sulfide adsorbent in the prior art are solved. , realizes accurate desulfurization and recycling at low temperatures, significantly reducing industrial costs.

CN119140060APending Publication Date: 2024-12-17INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310702688.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing hydrogen sulfide adsorbents have problems such as high use temperature, high cost, low desulfurization accuracy and harsh regeneration conditions, which are difficult to meet the high-efficiency and low-cost low-temperature desulfurization needs in the industry.

Method used

A low-temperature renewable adsorbent is prepared by using composite aluminosilicate with microporous/mesoporous channel structure as a carrier and combined with transition metal oxides as active components, which improves the diffusion rate and active components of hydrogen sulfide gas. The utilization rate of low-temperature precision desulfurization and recycling.

Benefits of technology

This adsorbent can achieve ppb-level desulfurization effect at low temperatures, reduce industrial use costs, and simple preparation process, avoid solid waste generation, and have significant economic and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140060A_ABST
    Figure CN119140060A_ABST
Patent Text Reader

Abstract

The invention provides a renewable adsorbent for removing hydrogen sulfide at low temperature as well as a preparation method and application thereof. The adsorbent consists of an active component and a carrier, the active component is a transition metal oxide, and the carrier is composite aluminosilicate with a microporous / mesoporous channel structure. The invention provides a renewable adsorbent for removing hydrogen sulfide at low temperature, the adsorbent takes composite aluminosilicate with a microporous / mesoporous channel structure as a carrier, the diffusion rate of hydrogen sulfide gas in the adsorbent is improved, and meanwhile, the utilization rate of active components is effectively improved; and the adsorbent can realize low-temperature fine desulfurization and regeneration cyclic utilization, so that the industrial use cost is effectively reduced. Therefore, the adsorbent has high application value and remarkable economic benefit and social benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent preparation, and in particular relates to a regenerable adsorbent for removing hydrogen sulfide at low temperature, and a preparation method and application thereof. Background Art

[0002] Hydrogen sulfide (H2S) is widely present in natural gas and secondary fuel gas such as coke oven and blast furnace gas, which use coal and natural gas as raw materials. The presence of hydrogen sulfide will not only corrode pipeline equipment, but also cause sulfur poisoning to the catalysts used in downstream process flows, making them inactive. In addition, the high sulfur content in the exhaust gas will cause serious damage to the environment. With the gradual strengthening of environmental protection policies, the effective use of high-sulfur combustible gases will be restricted. Therefore, the removal of hydrogen sulfide has important economic and social value.

[0003] At present, there are many methods for removing H2S waste gas at home and abroad, which can be divided into rough desulfurization, semi-fine desulfurization and fine desulfurization according to the desulfurization effect. According to the different desulfurization processes, it can be roughly divided into two categories: dry method and wet method. Wet desulfurization can meet the requirements of higher desulfurization load, but the desulfurization accuracy of this method is not high. In industry, the hydrogen sulfide content in the raw gas is often required to be as low as ppb level, so some dry desulfurizers with relatively high desulfurization accuracy should be used.

[0004] For example, patent US13395834B discloses a method for removing H2S from hydrocarbon streams, using zinc oxide to react with hydrogen sulfide to reduce the hydrogen sulfide content in the raw material to a certain range. CN106190340A discloses a composite metal oxide high-temperature coal gas desulfurizer. In order to meet the needs of industrial continuous production and to reduce the emission of solid waste, renewable H2S adsorbents have received increasing attention. CN109569498A discloses a method for preparing a renewable H2S adsorbent, which includes: 1. adding polyethylene glycol, tetraethyl orthosilicate and hexamethylenetetramine to a nitric acid solution and heating, then adding NH4OH and stirring, washing and drying to obtain powder I; 2. mixing aluminum sulfate, basic chromium sulfate, polyvinyl alcohol ammonium phosphate, diammonium hydrogen phosphate, sodium thiosulfate and anhydrous sodium carbonate evenly and roasting to obtain powder II; 3. mixing powder I and powder II evenly and adding sodium nitrate, and then calcining to obtain powder III; 4. grinding powder III to obtain a renewable hydrogen sulfide gas adsorbent. CN101805641B discloses an iron oxide-based high-temperature coal gas desulfurizer, which can be used at a temperature of 800°C and an air velocity of 3000h -1, the regeneration atmosphere is 15-28 vol.% O2 / SO2 and 72-85 vol.% N2 with a volume ratio of O2 / SO2 of 1:100. CN112295544A discloses a H2S adsorbent having a modified metal organic compound skeleton, a preparation method and an application thereof, the preparation method of the invention comprises heat treating a mixed solution containing an aluminum source, terephthalic acid, activated carbon and water, and then calcining to obtain a metal organic skeleton adsorbent.

[0005] Although the above-mentioned regenerable adsorbents can maintain the adsorption effect on H2S to a certain extent, they still have some defects, such as the complicated adsorbent preparation process, high manufacturing cost, only being able to be used at high temperatures, low desulfurization accuracy, and harsh regeneration conditions.

[0006] Therefore, how to solve the problems of high operating temperature, high cost, low desulfurization accuracy and harsh regeneration conditions existing in existing hydrogen sulfide adsorbents is a direction that urgently needs to be studied. Summary of the invention

[0007] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a regenerable adsorbent for removing hydrogen sulfide at low temperature, and a preparation method and application thereof. The present invention provides a regenerable adsorbent for removing hydrogen sulfide at low temperature, the adsorbent uses a composite aluminosilicate with a microporous / mesoporous channel structure as a carrier, improves the diffusion rate of hydrogen sulfide gas in the adsorbent, and effectively improves the utilization rate of active components, and the adsorbent can achieve low-temperature fine desulfurization and regeneration and recycling, which is simple and easy to operate, and effectively reduces the cost of industrial use. Therefore, the adsorbent has a strong application value, and significant economic and social benefits.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a regenerable adsorbent for removing hydrogen sulfide at low temperature, the adsorbent comprising a carrier and an active component supported on the carrier;

[0010] The active component is a transition metal oxide, and the carrier is a composite aluminosilicate with a microporous / mesoporous channel structure.

[0011] The present invention provides a regenerable adsorbent for removing hydrogen sulfide at low temperature. The adsorbent uses a composite aluminosilicate with a microporous / mesoporous channel structure as a carrier, which increases the diffusion rate of hydrogen sulfide gas in the adsorbent and effectively improves the utilization rate of active components. The adsorbent can achieve low-temperature fine desulfurization, and the desulfurization effect can reach ppb level. It can also achieve regeneration and recycling, which is simple and easy to operate, and effectively reduces the industrial use cost. Therefore, the adsorbent has a strong application value and significant economic and social benefits.

[0012] The adsorbent prepared by the invention can be used directly and can be regenerated after desorption, and the regeneration temperature is low and the operation is simple and easy.

[0013] In the present invention, abundant pores are beneficial to the diffusion of hydrogen sulfide gas in the adsorbent.

[0014] As a preferred technical solution of the present invention, the pore diameter of the micropore is 0.5-1 nm, for example, it can be 0.5 nm, 0.6 nm, 0.7 nm, 0.75 nm, 0.8 nm, 0.9 nm or 1 nm.

[0015] Preferably, the pore diameter of the mesopore is 2-5 nm, for example, 2 nm, 3 nm, 4 nm or 5 nm.

[0016] Preferably, the volume ratio of the micropores and the mesopores is (0.6-0.8):(0.4-0.2), wherein the selection range of the micropores "0.6-0.8" can be, for example, 0.6, 0.65, 0.7, 0.75 or 0.8, etc., and the selection range of the mesopores "0.4-0.2" can be, for example, 0.2, 0.25, 0.3, 0.35 or 0.4, etc.

[0017] In the present invention, if the volume ratio of micropores to mesopores is too small, that is, the content of micropores is too small, it is not conducive to the dispersion of modified transition metals and is easy to cause agglomeration of transition metal particles; if the volume ratio of micropores to mesopores is too large, that is, the content of micropores is too much, too many pores of the material will be blocked during the metal modification process, which is not conducive to the diffusion of gas during the adsorption-desorption regeneration process.

[0018] As a preferred technical solution of the present invention, the composite aluminosilicate includes at least one aluminosilicate, preferably two aluminosilicates.

[0019] The present invention adopts two kinds of aluminosilicates, which can simultaneously give the composite material microporous and mesoporous structures, so that the prepared adsorbent has a composite pore size, which is beneficial to the diffusion of gas during the material adsorption-desorption regeneration process.

[0020] Preferably, the chemical formula of the aluminosilicate is xAl2O3·ySiO2, y:x=0-100, for example, it can be 1, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.

[0021] Preferably, y:x=2-25.

[0022] Preferably, the composite aluminosilicate comprises a first aluminosilicate and a second aluminosilicate, and the y:x of the first aluminosilicate is greater than or equal to the y:x of the second aluminosilicate.

[0023] Preferably, the mass ratio of the first aluminosilicate to the second aluminosilicate is (2-6):1, for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, etc.

[0024] In the present invention, if the mass ratio of the first aluminosilicate to the second aluminosilicate is too small, that is, the amount of the first aluminosilicate used is too little, it is not conducive to the regeneration of the adsorbent; if the mass ratio of the first aluminosilicate to the second aluminosilicate is too large, that is, the amount of the first aluminosilicate used is too much, it is not conducive to the diffusion of the gas during the adsorption process.

[0025] As a preferred technical solution of the present invention, in the transition metal oxide, the transition metal includes any one or a combination of at least two of the fourth period, fifth period or sixth period transition metals, preferably any one or a combination of at least two of copper, zinc, silver, cobalt, iron or nickel, and more preferably copper and zinc.

[0026] In the present invention, copper and zinc are simultaneously present in the active component, which can play a synergistic role and is beneficial to improving the hydrogen sulfide adsorption capacity per unit volume and mass.

[0027] Preferably, the copper-zinc atomic ratio of the copper and zinc is (0.9-0.6):(0.1-0.3), wherein the selection range of copper "0.9-0.6" can be, for example, 0.9, 0.8, 0.7 or 0.6, etc., and the selection range of zinc "0.1-0.3" can be, for example, 0.1, 0.2 or 0.3, etc.

[0028] Preferably, the mass percentage of the active component and the carrier is (10-50):(90-50), wherein the selection range of the active component "10-50" can be, for example, 10, 20, 30, 40 or 50, etc., and the selection range of the carrier "90-50" can be, for example, 50, 60, 70, 80 or 90, etc.

[0029] As a preferred technical solution of the present invention, the temperature range of low-temperature removal of hydrogen sulfide is 70-150°C, for example, it can be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0030] The adsorbent provided by the present invention can remove hydrogen sulfide within the range of 70-150°C, and can remove nearly 100% of the hydrogen sulfide in the mixed gas. If the removal temperature is too high, the desorption of hydrogen sulfide will be accelerated and its adsorption capacity will be reduced. At the same time, high temperature will lead to excessively high energy costs, which is not conducive to industrial applications.

[0031] In a second aspect, the present invention provides a method for preparing the adsorbent according to the first aspect, the preparation method comprising the following steps:

[0032] The composite aluminosilicate, transition metal salt and solvent are mixed to react, and then calcined to obtain the adsorbent.

[0033] The adsorbent provided by the present invention has a simple preparation process, does not require the use of organic harmful reagents during the preparation process, can be recycled and reused, avoids the generation of solid waste, and is an environmentally friendly material.

[0034] The adsorbent preparation process provided by the present invention belongs to dry desulfurization, which overcomes the problems of low desulfurization accuracy in wet desulfurization technology.

[0035] As a preferred technical solution of the present invention, the transition metal salt includes any one of acetate, sulfate or nitrate, or a combination of at least two of them.

[0036] Preferably, the solvent comprises water.

[0037] The present invention does not impose any particular limitation on water, and illustratively, it may be ultrapure water.

[0038] Preferably, the mixing process is accompanied by stirring.

[0039] Preferably, the specific manner of mixing includes:

[0040] (a) dissolving a transition metal salt in a solvent to obtain a transition metal salt solution;

[0041] (b) blending the composite aluminosilicate and the transition metal salt solution.

[0042] The present invention adopts this mixing method to load the transition metal on the surface of the aluminosilicate carrier to the maximum extent, which is beneficial to the dispersion of the metal.

[0043] Preferably, in step (b), the volume ratio of the composite aluminosilicate to the transition metal salt solution is 1:(1-5), for example, it can be 1:1, 1:2, 1:3, 1:4 or 1:5.

[0044] As a preferred technical solution of the present invention, the reaction temperature is room temperature.

[0045] In the present invention, room temperature refers to 25±5°C, for example, it may be 20°C, 22°C, 24°C, 26°C, 28°C or 30°C.

[0046] Preferably, the reaction time is 8-12 h, for example, 8 h, 9 h, 10 h, 11 h or 12 h.

[0047] Preferably, the calcination temperature is 350-650°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, etc., preferably 450-600°C.

[0048] In the present invention, if the calcination temperature is too low, the metal cannot be completely converted into an oxide with an adsorption effect, and the hydrogen sulfide adsorption capacity is reduced; if the calcination temperature is too high, it is easy to cause the metal oxide particles to agglomerate, the effective adsorption sites are reduced, and the hydrogen sulfide adsorption capacity is reduced.

[0049] Preferably, the calcination time is 3-6 h, for example, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc., preferably 3.5-4.5 h.

[0050] Preferably, the calcining atmosphere is an air atmosphere.

[0051] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0052] (1) dissolving a transition metal salt in a solvent to obtain a transition metal salt solution, stirring and dispersing at least one aluminosilicate in the transition metal salt solution at room temperature for a reaction of 8-12 hours, evaporating the solvent at 70-90° C. after the reaction, and then drying at 100-120° C. for 3-6 hours;

[0053] (2) calcining the dried product in an air atmosphere for 3-6 hours at a calcination temperature of 350-650° C. to obtain the adsorbent;

[0054] Wherein, the heating rate of the calcination temperature is 2-4°C / min.

[0055] In the present invention, 70-90°C may be, for example, 70°C, 75°C, 80°C, 85°C or 90°C, etc., 100-120°C may be, for example, 100°C, 105°C, 110°C, 115°C or 120°C, etc., and drying may be for 3-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, etc.

[0056] In a third aspect, the present invention provides a use of the adsorbent as described in the first aspect, wherein the adsorbent is used to remove hydrogen sulfide from blast furnace gas, coke oven gas or fuel gas.

[0057] In the present invention, the blast furnace gas contains hydrogen, methane, carbon monoxide, carbon dioxide and oxygen in addition to hydrogen sulfide, and the coke oven gas contains hydrogen, methane, carbon monoxide, carbon dioxide and oxygen in addition to hydrogen sulfide.

[0058] It should be noted that the use condition of the adsorbent provided by the present invention is 60-90°C, for example, it can be 60°C, 70°C, 80°C or 90°C.

[0059] In the present invention, when the adsorbent is regenerated, the bed is heated with a carrier at 160-280°C to desorb the adsorbed hydrogen sulfide and restore the adsorption capacity of the adsorbent for hydrogen sulfide. The regeneration gas used is selected from hydrogen, methane, carbon monoxide, carbon dioxide or oxygen after the hydrogen sulfide is removed.

[0060] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) The present invention provides a regenerable adsorbent for removing hydrogen sulfide at low temperature. The adsorbent uses a composite aluminosilicate with a microporous / mesoporous channel structure as a carrier, which improves the diffusion rate of hydrogen sulfide gas in the adsorbent and effectively improves the utilization rate of active components. The adsorbent can achieve low-temperature fine desulfurization, and the desulfurization effect can reach ppb level. It can also be regenerated and recycled. The regeneration temperature is low, simple and easy to operate, and effectively reduces the industrial use cost.

[0063] (2) The adsorbent provided by the present invention has a simple preparation process, does not require the use of organic hazardous reagents during the preparation process, and can be recycled and reused, thus avoiding the generation of solid waste, and is an environmentally friendly material.

[0064] (3) The adsorbent provided by the present invention has strong application value and significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is the pore size distribution diagram of adsorbent A prepared in Example 1 of the present invention.

[0066] Figure 2 This is a comparison chart of the breakthrough curves of adsorbent A, adsorbent B and adsorbent C prepared in Examples 1-3 of the present invention for absorbing hydrogen sulfide.

[0067] Figure 3 This is a comparison chart of the breakthrough curves of adsorbent A, adsorbent D and adsorbent E prepared in Examples 1, 4 and 5 of the present invention for absorbing hydrogen sulfide.

[0068] Figure 4 This is a breakthrough curve diagram of the adsorbent prepared in Example 1 of the present invention after three cycles of regeneration. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] Example 1

[0071] This embodiment provides a regenerable adsorbent for removing hydrogen sulfide at low temperature, the adsorbent comprising a carrier and an active component loaded on the carrier, the active component is a transition metal oxide, and the carrier is a composite aluminosilicate having a microporous / mesoporous channel structure;

[0072] Among them, the pore diameter of the micropores is 0.5-1nm, the pore diameter of the mesopores is 2-5nm, and the volume ratio of the micropores to the mesopores is 4:1; the composite aluminosilicate includes a first aluminosilicate with y:x=25 and a second aluminosilicate with y:x=2, and the mass ratio of the two is 3:1; the transition metal oxide includes copper oxide and zinc oxide with a copper-zinc atomic ratio of 3:1, and the mass percentage of the composite aluminosilicate and the transition metal oxide is 83:17.

[0073] The present invention also provides a method for preparing the above-mentioned regenerable adsorbent for removing hydrogen sulfide at low temperature, the preparation method comprising the following steps:

[0074] (1) dissolving 5.6 g of copper nitrate and 1.4 g of zinc nitrate in 60 mL of ultrapure water to obtain a transition metal salt solution;

[0075] (2) adding 7.5 g of the first aluminosilicate and 2.5 g of the second aluminosilicate to the transition metal salt solution, and stirring for 10 h at room temperature (25° C.) to react. After the reaction, evaporating the solvent ultrapure water in a water bath at 80° C., and then drying in an oven at 105° C. for 3 h;

[0076] Wherein, the volume ratio of the total volume of the first aluminosilicate and the second aluminosilicate to the transition metal salt solution is 1:3;

[0077] (3) The dried sample was poured into a crucible, placed in a muffle furnace at 550° C., and calcined in an air atmosphere for 4 h at a heating rate of 3° C. / min. The sample was then mechanically pressed into tablets and sieved through 40 mesh to obtain the regenerable adsorbent for low-temperature removal of hydrogen sulfide, which was recorded as adsorbent A.

[0078] The adsorbent A provided in this embodiment can remove hydrogen sulfide at 110°C.

[0079] Figure 1 The pore size distribution diagram of the adsorbent A prepared in this example is shown. It can be seen from the figure that the prepared adsorbent has a microporous and mesoporous structure, and the volume ratio of micropores to mesopores is 4:1.

[0080] Example 2

[0081] The difference between this embodiment and embodiment 1 is that in step (1), only 7 g of copper nitrate is added to ultrapure water, that is, the active component of the obtained adsorbent contains only copper oxide, and this adsorbent is recorded as adsorbent B.

[0082] The rest of the preparation methods and parameters were the same as those in Example 1.

[0083] Example 3

[0084] The difference between this embodiment and embodiment 1 is that in step (1), only 7 g of zinc nitrate is added to ultrapure water, that is, the active component of the obtained adsorbent contains only zinc oxide, and this adsorbent is recorded as adsorbent C.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Figure 2 A comparison of the breakthrough curves of the adsorbents prepared in Examples 1-3 for absorbing hydrogen sulfide is shown. It can be seen from the figure that compared with the single metal adsorbent, the adsorbent containing copper and zinc has a larger hydrogen sulfide adsorption capacity, indicating that the two metals have a synergistic effect in the adsorption process.

[0087] Example 4

[0088] The difference between this embodiment and embodiment 1 is that in step (2), only the first aluminosilicate is added to the transition metal salt solution, that is, the carrier of the obtained adsorbent is only composed of the first aluminosilicate, and the adsorbent is recorded as adsorbent D.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Example 5

[0091] The difference between this embodiment and embodiment 1 is that in step (2), only the second aluminosilicate is added to the transition metal salt solution, that is, the carrier of the obtained adsorbent is only composed of the second aluminosilicate, and the adsorbent is recorded as adsorbent E.

[0092] The rest of the preparation methods and parameters were the same as those in Example 1.

[0093] Figure 3 A comparison of the penetration curves of hydrogen sulfide absorption by the adsorbents prepared in Example 1, Example 4 and Example 5 is shown. It can be seen from the figure that compared with a single aluminosilicate carrier, the composite carrier of two aluminosilicates has a higher hydrogen sulfide adsorption capacity, which can be attributed to the composite carrier having a richer pore structure, which is conducive to the dispersion of metals and the diffusion of hydrogen sulfide gas.

[0094] Example 6

[0095] The difference between this embodiment and embodiment 1 is that the volume ratio of micropores and mesopores in the composite aluminosilicate is 2:3 by adjusting the ratio of the two aluminosilicates and y to x.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Example 7

[0098] The difference between this embodiment and embodiment 1 is that the volume ratio of micropores and mesopores in the composite aluminosilicate is 5:1 by adjusting the ratio of the two aluminosilicates and y to x.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 8

[0101] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of the first aluminosilicate to the second aluminosilicate is 1:1.

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Example 9

[0104] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of the first aluminosilicate to the second aluminosilicate is 7:1.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Example 10

[0107] The difference between this embodiment and embodiment 1 is that in this embodiment, copper nitrate, zinc nitrate, the first aluminosilicate, the second aluminosilicate and ultrapure water are directly mixed.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Embodiment 11

[0110] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is 300°C.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] Example 12

[0113] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (3) is 700°C.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Comparative Example 1

[0116] The difference between this comparative example and Example 1 is that the carrier does not have a microporous channel structure by adjusting the ratio of y to x in the aluminosilicate.

[0117] The rest of the preparation methods and parameters were the same as those in Example 1.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 1 is that the carrier does not have a mesoporous channel structure by adjusting the ratio of y to x in the aluminosilicate.

[0120] The rest of the preparation methods and parameters were the same as those in Example 1.

[0121] Performance Testing

[0122] The adsorbents prepared in Examples 1-12 and Comparative Examples 1-2 were analyzed and tested. The hydrogen sulfide concentration was tested using an online chromatograph, and when the H2S concentration detected at the outlet was 10% of the initial concentration, the adsorbent was defined to have been penetrated, and the time required for penetration was the penetration time, which was used to determine the adsorption effect of the adsorbent material.

[0123] Test process: The hydrogen sulfide adsorption effect was tested in a fixed bed quartz reactor with a catalyst loading of 1 cm 3 , height is about 1.27cm, particle size is 30-50 mesh, reaction temperature is 80℃, heating rate is 3℃ / min. Standard gas is hydrogen sulfide with concentration of 1000ppm, diluent gas is simulated gas (components: carbon dioxide, oxygen, methane, hydrogen, carbon monoxide and nitrogen), standard gas and simulated gas are introduced into the reactor at a ratio of 2:8, total gas flow rate is 100mL / min (standard gas 20mL / min, simulated gas 80mL / min), and the temperature of the reaction device is kept at 80℃ for testing.

[0124] The calculation formula of hydrogen sulfide adsorption penetration rate is:

[0125] H2S penetration rate (%) = outlet concentration of raw gas / inlet concentration of raw gas × 100%

[0126] The test results are shown in Table 1.

[0127] Table 1

[0128]

[0129]

[0130] The regeneration process of the adsorbent is as follows: stop introducing the standard gas, adjust the simulated dilution gas flow to 10 mL / min, heat the fixed bed reactor from the adsorption temperature to 180°C through a heating furnace over 240 minutes, keep the temperature at 180°C for 300 minutes, then heat to 240°C in 240 minutes, keep the temperature at 240°C for 360 minutes, then heat to 280°C in 180 minutes, keep the temperature at 800 minutes, then cool naturally, and after dropping to 80°C, test the adsorption effect of the adsorbent again according to the test conditions.

[0131] Figure 4 The breakthrough curve diagram of the adsorbent prepared in Example 1 after three cycles of regeneration is shown. It can be seen from the figure that the performance of the prepared adsorbent after cyclic regeneration decreases slightly in the initial stage and then tends to be stable.

[0132] The test results are shown in Table 2.

[0133] Table 2

[0134]

[0135] analyze:

[0136] As can be seen from Table 1 and Table 2, the present invention provides a regenerable adsorbent for removing hydrogen sulfide at low temperature, the adsorbent uses a composite aluminosilicate with a microporous / mesoporous channel structure as a carrier, improves the diffusion rate of hydrogen sulfide gas in the adsorbent, and effectively improves the utilization rate of active components, and the adsorbent can achieve low-temperature fine desulfurization and regeneration and recycling, which is simple and easy to operate, and effectively reduces the industrial use cost. Therefore, the adsorbent has a strong application value, and significant economic and social benefits.

[0137] It can be seen from the data results of Example 1 and Example 2-3 that if the active component contains only one transition metal oxide, no synergistic effect can be produced, resulting in poor adsorption effect and small regenerated sulfur capacity after regeneration.

[0138] It can be seen from the data results of Examples 1 and 4-5 that if the carrier is composed of only one type of aluminosilicate, it is not conducive to the dispersion of transition metals and gas diffusion during the adsorption-desorption process, resulting in a reduced adsorption effect and a poor regeneration effect after regeneration.

[0139] It can be seen from the data results of Example 1 and Examples 6-7 that if the volume ratio of micropores to mesopores is too small, it will be unfavorable for the dispersion of transition metals, resulting in a weakened adsorption effect, and the adsorption effect will also be weakened after regeneration; if the volume ratio of micropores to mesopores is too large, it will be unfavorable for gas expansion, resulting in a weakened adsorption effect, and the regeneration effect will also be weakened.

[0140] It can be seen from the data results of Example 1 and Examples 8-9 that if the mass ratio of the first aluminosilicate to the second aluminosilicate is too small, the adsorption effect decreases, and the adsorption effect also decreases after regeneration; if the mass ratio of the first aluminosilicate to the second aluminosilicate is too large, the adsorption effect decreases, and the adsorption effect also decreases after regeneration.

[0141] It can be seen from the data results of Example 1 and Example 10 that if copper nitrate, zinc nitrate, the first aluminosilicate, the second aluminosilicate and ultrapure water are directly mixed, it is not conducive to the dispersion of transition metals on the adsorbent surface and the adsorption effect is weakened.

[0142] It can be seen from the data results of Example 1 and Examples 11-12 that if the calcination temperature is too low, the loaded transition metal cannot be completely converted into oxides, resulting in a decrease in the adsorption effect, and the adsorption effect is also reduced after regeneration; if the calcination temperature is too high, the metal oxides will agglomerate, resulting in a decrease in the adsorption effect, and the adsorption effect is also reduced after regeneration.

[0143] It can be seen from the data results of Example 1 and Comparative Examples 1-2 that if the carrier does not have a microporous channel structure or does not have a mesoporous channel structure, it is not conducive to metal dispersion or gas diffusion, resulting in a weakened adsorption effect, and the adsorption effect is weakened after regeneration.

[0144] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A regenerable adsorbent for removing hydrogen sulfide at low temperature, characterized in that: The adsorbent includes a carrier and an active component loaded on the carrier; The active component is a transition metal oxide, and the carrier is a composite aluminosilicate with a microporous / mesoporous channel structure.

2. The adsorbent according to claim 1, characterized in that The pore diameter of the micropore is 0.5-1 nm; Preferably, the pore diameter of the mesopores is 2-5 nm.

3. The adsorbent according to claim 1 or 2, characterized in that The composite aluminosilicate comprises at least one aluminosilicate, preferably two aluminosilicates; Preferably, the chemical formula of the aluminosilicate is xAl2O3·ySiO2, y:x=0-100; Preferably, y:x=2-25; Preferably, the composite aluminosilicate comprises a first aluminosilicate and a second aluminosilicate, and the y:x of the first aluminosilicate is greater than or equal to the y:x of the second aluminosilicate; Preferably, the mass ratio of the first aluminosilicate to the second aluminosilicate is (2-6):

1.

4. The adsorbent according to any one of claims 1 to 3, characterized in that In the transition metal oxide, the transition metal includes any one or a combination of at least two of the fourth period, fifth period or sixth period transition metals, preferably any one or a combination of at least two of copper, zinc, silver, cobalt, iron or nickel, more preferably copper and zinc; Preferably, the mass percentage of the active ingredient and the carrier is (10-50):(90-50).

5. The adsorbent according to any one of claims 1 to 4, characterized in that The temperature range of the low-temperature removal of hydrogen sulfide is 70-150°C.

6. A method for preparing an adsorbent according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The composite aluminosilicate, transition metal salt and solvent are mixed to react, and then calcined to obtain the adsorbent.

7. The preparation method according to claim 6, characterized in that: The transition metal salt includes any one of acetate, sulfate or nitrate or a combination of at least two thereof; Preferably, the solvent comprises water; Preferably, the mixing process is accompanied by stirring; Preferably, the specific manner of mixing includes: (a) dissolving a transition metal salt in a solvent to obtain a transition metal salt solution; (b) blending the composite aluminosilicate and the transition metal salt solution; Preferably, in step (b), the volume ratio of the composite aluminosilicate to the transition metal salt solution is 1:(1-5).

8. The preparation method according to claim 6 or 7, characterized in that: The reaction temperature is room temperature; Preferably, the reaction time is 8-12h; Preferably, the calcination temperature is 350-650°C, preferably 450-600°C; Preferably, the calcination time is 3-6h, preferably 3.5-4.5h; Preferably, the calcining atmosphere is an air atmosphere.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method comprises the following steps: (1) dissolving a transition metal salt in a solvent to obtain a transition metal salt solution, stirring and dispersing at least one aluminosilicate in the transition metal salt solution at room temperature for a reaction of 8-12 hours, evaporating the solvent at 70-90° C. after the reaction, and then drying at 100-120° C. for 3-6 hours; (2) calcining the dried product in an air atmosphere for 3-6 hours at a calcination temperature of 350-650° C. to obtain the adsorbent; Wherein, the heating rate of the calcination temperature is 2-4°C / min.

10. Use of the adsorbent according to any one of claims 1 to 5, characterized in that: The adsorbent is used for removing hydrogen sulfide from blast furnace gas, coke oven gas or fuel gas.